1980
DOI: 10.1111/j.1398-9995.1980.tb01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Aeruginosa Allergy in Cystic Fibrosis

Abstract: Basophil histamine release by P. aeruginosa standard antigen was examined in cystic fibrosis patients chronically infected with mucoid P. aeruginosa (CF +P) and with pronounced antibody response against these bacteria, and in patients without P. aeruginosa infection (CF +P). All the patients showed eosinophil counts and total IgE, which did not differ significantly from that of normal persons. In the absence of patient's sera, histamine release was only found in two patients in the CF +P group, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…By incubating P. aeruginosa standard antigens in the presence of 10% of the patients' sera, histamine release from basophils was obtained in 50% of the GF-(-P patients, whereas no release was observed when sera were complement-inactivated. It was therefore suggested that a type Ill-mediated complement-dependent histamine release was involved in the pathogenesis of the lung damage in GF-fP patients (11). It is, however, possible that the immune complexes can mediate the release of other vasoactive amines, which could also be responsible for the allergic-inflammatory reactions.…”
Section: Disgussionmentioning
confidence: 79%
See 3 more Smart Citations
“…By incubating P. aeruginosa standard antigens in the presence of 10% of the patients' sera, histamine release from basophils was obtained in 50% of the GF-(-P patients, whereas no release was observed when sera were complement-inactivated. It was therefore suggested that a type Ill-mediated complement-dependent histamine release was involved in the pathogenesis of the lung damage in GF-fP patients (11). It is, however, possible that the immune complexes can mediate the release of other vasoactive amines, which could also be responsible for the allergic-inflammatory reactions.…”
Section: Disgussionmentioning
confidence: 79%
“…In a previous study we have found that in vitro formation of immune complexes induced a complement-mediated release of histamine in these patients (11). By incubating P. aeruginosa standard antigens in the presence of 10% of the patients' sera, histamine release from basophils was obtained in 50% of the GF-(-P patients, whereas no release was observed when sera were complement-inactivated.…”
Section: Disgussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Precise information of lhe causative agent, evaluation of the degree of allergy and of the improvement by immunotherapy (12) and furthermore, estimation of blocking antibodies (11). The basophil histamine release has been found useful in the diagnosis of house dust, mite, animal dandruff, pollen and mould fungi (15). Investigations are now being made in our laboratory for testing drugs (6), foods, bacterial antigens (15) and autoimmune allergies (4) for diagnostics of type I reactions.…”
Section: Disadvantages Of These Systemsmentioning
confidence: 99%